Fourier Transform Infrared Macro-Imaging of Botanical Cotton Trash. Issue 6 (November 2015) - Fortier, Chanel; Cintròn, Michael Santiago; Rodgers, James
The marketability of cotton fiber is directly tied to the trash comingled with it. Trash can contaminate cotton during harvesting, ginning, and processing. Thus, the removal of trash is important from field to fabric. An ideal prerequisite to removing trash from lint is identifying what trash types are present. A relatively new and fast analytical technique has been gaining popularity among researchers is hyperspectral imaging. Coupling Fourier-transform infrared (FTIR) imaging with attenuated total reflectance (ATR) and a focal plane array (FPA) detector allows for larger samples to be analyzed with speed and little to no sample preparation. It is the goal of this study to identify botanical trash using hyperspectral FTIR imaging as a feasibility study to facilitate wider utility of this method in the textile field and to use this data to create a spectral library.